TLR9 agonist produces effective mucosal immunity as a vaccine against Mycobacterium tuberculosis - Troy, Amber, author; Izzo, Angelo, advisor; McLean, Jennifer, committee member; Biller, Barbara, committee member; Zabel, Mark, committee member (Colorado State University. Libraries, 2016)
The Mycobacterium tuberculosis bacillus has plagued the world for thousands of years. Researchers have found evidence of tuberculosis infection as far back as the Ice-Ages with the presence of bone lesions in mastodons. The existence of tuberculosis in humans has also been found in ancient Egyptian mummies dating as far back as 4000 years ago. Pulmonary tuberculosis is an airborne bacterial disease and the causative agent, M. tuberculosis, currently infects about 2-3 billion people globally. This deadly disease is responsible for killing an average of 5,000 people every single day, and is most prevalent in developing countries, particularly in sub-Saharan Africa where the AIDS epidemic grows yearly. TB is one of the first diseases to arise in these immune-suppressed patients, which furthers the need for a new effective disease control strategy. The incidence of drug resistance has been increasing steadily, also exemplifying the need for a prophylactic approach to combating the disease. The only currently available vaccine for M. tuberculosis in use today is Mycobacterium bovis Bacillus Calmette-Guérin (BCG), a live attenuated vaccine that has been in use since the 1930’s, and with a variable efficacy rate of 0-80% the need for a new more effective vaccine is dire. BCG is the mostly widely used vaccine in the world with some success in young children, but immunity wanes over time due to a number of reasons. In order to replace BCG or boost BCG, a better understanding of the immune response is required, allowing for better vaccine development. Animal models provide a good basis for determining immune mechanisms that are related to protective immunity, both innate and adaptive. Toll-like receptors (TLRs) are a key component of the innate immune response. TLRs are pattern recognition receptors (PRR), which recognize pathogen associated molecular patterns (PAMPs). These PAMPs are not produced by mammalian cells but are presented by invading microorganisms. Once PAMPs are detected the innate immune response is activated and begins the clearance of bacterial infection. PRRs are also required to activate antigen-presenting cells (APCs) that process bacterial antigens for presentation, in association with major histocompatibility complexes (MHC) to T-cells. One particularly stimulatory PAMP is CpG Oligodeoxynucleotide (ODN), which is unmethylated bacterial DNA. Once CpG ODN is introduced, the PRR TLR9 is activated thus inducing a potent T-helper 1 (Th1) response which plays a critical role in tuberculosis infection. Mucosally administered vaccines have been of particular interest to vaccine researches in the past twenty years. Data show the nasal mucosa is an effective route of vaccine administration because it is the first point of contact to an inhaled pathogen. Since pulmonary tuberculosis is spread via aerosolized particles, vaccines targeting the mucosa may effectively prime local antigen presenting cells like alveolar macrophages and dendritic cells. One method for vaccine delivery is the use of a carrier vehicle such as cationic liposomes. Cationic liposomes consist of a positively charged lipid bi-layer. The positive charge on these liposomes allows the addition of a negatively charged immune-stimulant such as CpG ODN. Liposomes carrying antigen are capable of inducing a robust cell mediated immune response or Th1 type response, which is crucial for mitigating M. tuberculosis infection. Since protein antigen degradation occurs quickly in mucosal sites liposomes provide increased stability of these vaccine components and thus allowing prolonged antigen presentation. Given that tuberculosis is a pulmonary infection, we hypothesize that targeting the site of infection with a TLR9 agonist; a robust mucosal immune response would be induced providing protection against infection and reducing bacterial burden. Using the mouse model of tuberculosis, we determined that intranasal inoculation of a cationic liposome carrying CpG ODN and the M. tuberculosis antigen ESAT-6 provides protection by inducing a robust Th1-type immune response capable of significantly reducing mycobacterial burden in the lungs after pulmonary infection, and also creating long-lasting immunity by stimulating the activation of memory T-cells.